A Cross-Sectional Study of The Relationship Between Job Stress and Nurse Performance in The Inpatient Ward of Wijaya Kusuma Hospital - Tri Sumarni; Amelia Andini (Viva Medika, 2025)
Nursing services in hospitals are an integral part of health services. A nurse has contact with patients within 24 hours, and the demands of the job are potentially stressful. Poor job performance among nurses can be caused by job stress. This study aims to determine the relationship between job stress and nurse performance. This study is a descriptive correlational study with a cross sectional approach. The sampling technique used a total sampling technique of 79 nurses.  The research instrument was a Nursing Stress Scale (NSS) questionnaire of 33 questions and nurse performance assessed by the head of the room as many as three aspects assessed (behavior, professional ability, nursing process). Bivariate analysis using spearman rank statistical test. Nurses' job stress was mostly in the normal category (83.5%). The majority of respondents' performance was in the good category (88%). There is a negative relationship between work stress and nurse performance, the higher the nurse's work stress, the lower the nurse's performance (p value=0.027, r=0.-249). The findings are based on a relatively small and homogenous sample, which may limit the generalizability to other populations. The need for management at Wijaya Kusuma Hospital to pay attention to all dimensions of work stress, and elements that contribute to improving nurse performance and conduct stress management training such as mindfulness or coping mechanism training and conduct outbound activities for nurses.